REKONSEPSI MODEL PEMBELAJARAN KONTEMPORER BERBASIS ADABI AL-IJTIMA’I (Studi Pembelajaran Hadist di MAN 3 Malang) - Khamim Khamim (LP. Ma'arif Janggan Magetan, 2020)
Abstract: This study reveals the methods of learning contemporary Hadith with the approach of adabi al-Ijtima'I at MAN 3 Malang. This research is qualitative in nature with a descriptive analysis approach with data mining techniques observation, interviews, and documentation. The results of the study found that the learning model of Hadith, namely: First, the nonlinguistic learning model, which has three elements, namely; 1) eliminating barriers in learning, 2) revealing meaning through analysis (meaning analysis) by means of Hadith text analysis; 3) meaning and historical. Understanding students by presenting history and uncovering meaning with stories. Second, the adabi al-Ijtima'i approach focuses on the integration of social systems with texts that include; 1) integrative between text and social system (text and social integration), that is understanding the text of Hadith with social interpretation; 2) norm integrality, ie educators understand the Hadith text in relation to social norms; 3) a description of the social context which describes the text of the common Hadith, into specific social spaces based on phenomena. Abstrak: Penelitian ini mengungkap metode pembelajaran Hadis kontemporer dengan pendekatan adabi al-Ijtima’I di MAN 3 Malang, Penelitian ini bercorak kualitatif dengan pendekatan deskriptif analisis dengan teknik penggalian datanya observasi, wawancara, dan dokumentasi. Hasil penelitian menemukan, bahwa model pembelajaran Hadis, yaitu: Pertama, model pembelajran nonlingustik, yang memiliki tiga unsur, yaitu; 1) menghilangkan sekat kebahasan dalam pembelajaran, 2) mengungkap makna dengan analisis (meaning analysis) dengan cara analisis teks Hadis; 3) makna dan historis. Memahamkan anak didik dengan cara menyajikan sejarah dan mengungkap makna dengan kisah. Kedua, pendekatan adabi al-Ijtima’i memfokuskan pada integrasi sistem sosial dengan teks yang mencakup; 1) integratif antara teks dengan sistem sosial (text and social integration), yaitu memahami teks Hadis dengan penafsiran sosial; 2) integrarif norma, yaitu pendidik memahamkan teks Hadis dihubungan dengan norma sosial; 3) deskripsi konteks sosial yang menjabarkan teks Hadis yang umum, ke dalam ruang-ruang sosial yang khusus berdasar fenomena.